PENENTUAN ZONASI POTENSI MINERAL LOGAM DI DAIRI SUMATRA UTARA BERDASARKAN DATA GEOSAINS TERINTEGRASI: DETERMINATION OF THE POTENTIAL ZONING OF METALLIC MINERALS IN DAIRI NORTH SUMATRA BASED ON INTEGRATED GEOSCIENCE - Nazirah Saina; Dzil Mulki Heditama; Iwan Nursahan; Prihadi Sumintadiredja (Buletin Sumber Daya Geologi, 2025)
Based on previous investigations by PSDMBP The Dolok Pangkuruhan area in Dairi Regency is known to have prospects for gold and other metal minerals deposits. This study aims to analyze the characteristics of mineralization and alteration, as well as to determine the potential zones of metal minerals through the integration of geological, geochemical, and geophysical data. The analytical methods used in this study include petrography, mineragraphy, X-ray Diffraction (XRD), Portable Infrared Mineral Analyzer (PIMA), statistical geochemistry, and geoelectric methods, specifically Induced Polarization (IP) and Resistivity. The results show three main lithological formations: phyllite, metasedimentary sandstone, and tuff. The types of alteration identified in the study area include argillic (illite-halloysite-kaolinite), argillic-propylitic (illite-intchlorite), phyllic (quartz-pyrite-chlorite), and phyllic-silicified (quartz-muscovite-illite). Based on the integration of geological, geochemical, and geophysical data, the potential metal mineral zones were identified in the subsurface six lines, specifically at line 5 prospect zone (Zn-Pb-Ag) and line 8 prospect zone (Au-Pb). Each line exhibits high chargeability values (100-190 ms) and moderate to high resistivity values (100-31623 ohm.m). The element concentration with the highest value of Zn is (11000 ppm), Pb ranges from (2324-4753 ppm), Au concentrations range from (1525-3 ppm) and Ag concentrations are the smallest, ranging from (10-25 ppm).